Disaster Specific Approaches: Chemical, Biological, Radiation and Nuclear (CBRN) Disasters: Strategies and Stakeholders in Addressing CBRN Disasters (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The probability of a NBC emergencydisaster is quite low, however it can’t be completely ruled out. Consequent to the National Disaster Management Act, 2005 the raising of NDRF has brought about a paradigm shift in the way the country now plans to respond to a disaster situation. However, despite all the enunciated measures, the likely commitment of the Armed Forces in fighting the disasters in the country continues to remain irrefutable. Even though the NDMA mandates the status for secondary responder for the Armed Forces, they may in certain situations, continue to remain the sole instrument of launching relief operations given their reach, size resources. However, due to complex nature of CBRN (Chemical, Biological, and Radiation Nuclear) emergency the extent pan India footprint of Armed Forces can contribute very effectively to mitigate a CBRN disaster. It further underlines the requirement of Armed Forces in support of civil administration to fully prepare for response to CBRN disasters irrespective of statusobligation of responders. The paper presentation will cover the following nuances a)CBRN EmergenciesDisasters b)Levels of Disaster c)Role of various stakeholders d)Initial Actions e)Media Assistance from Civil Administration